2018
DOI: 10.1093/gbe/evy259
|View full text |Cite
|
Sign up to set email alerts
|

ThePseudomonas aeruginosaPan-Genome Provides New Insights on Its Population Structure, Horizontal Gene Transfer, and Pathogenicity

Abstract: The huge increase in the availability of bacterial genomes led us to a point in which we can investigate and query pan-genomes, for example, the full set of genes of a given bacterial species or clade. Here, we used a data set of 1,311 high-quality genomes from the human pathogen Pseudomonas aeruginosa, 619 of which were newly sequenced, to show that a pan-genomic approach can greatly refine the population structure of bacterial species, provide new insights to define species boundaries, and generate hypothese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
261
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(290 citation statements)
references
References 44 publications
24
261
4
1
Order By: Relevance
“…We analyzed public available genome sequencing data on a collection of 1,139 isolates that have previously been included in a pan-and core genome analysis by Freschi et al (2019) [19], to compare the pan-and core genome sizes between different collections of isolates. When we used the same method as for our own isolate collection (GenAPI), we found that the 1,139 isolates from Pan-and core genomes…”
Section: Core Genome Snp Distances To Define Clone Typesmentioning
confidence: 99%
“…We analyzed public available genome sequencing data on a collection of 1,139 isolates that have previously been included in a pan-and core genome analysis by Freschi et al (2019) [19], to compare the pan-and core genome sizes between different collections of isolates. When we used the same method as for our own isolate collection (GenAPI), we found that the 1,139 isolates from Pan-and core genomes…”
Section: Core Genome Snp Distances To Define Clone Typesmentioning
confidence: 99%
“…A cohort of 558 clinical and 172 environmental genome assemblies of P. aeruginosa isolates from multiple countries were used in this study (Table S2) (78,79). Clinical isolates were from patients with cystic fibrosis, bronchiectasis or chronic obstructive pulmonary disease.…”
Section: Clinical and Environmental Isolates Of P Aeruginosamentioning
confidence: 99%
“…Genome assemblies of clinical and environmental isolates have been described previously (78,79) (Table S2). For experimentally evolved mutants and clinical isolates sequenced in this study, genomic DNA was extracted from overnight cultures of endpoint resistant mutants using the MoBio UltraClean® Microbial DNA isolation kit.…”
Section: Whole Genome Sequencingmentioning
confidence: 99%
“…LGT is an important evolutionary force in prokaryotes, with up to 60% of genes within a species pangenome being acquired in this manner (Freschi et al 2018). The genes transferred can have a dramatic effect on adaptation, facilitating the colonisation of new niches and the development of novel phenotypes, as exemplified by the rapid spread of antibiotic resistance in bacteria (Ochman et al 2000).…”
Section: Introductionmentioning
confidence: 99%